Toward the Interpretation of Positive Testing for Fentanyl and Its Analogs in Real Hair Samples: Preliminary Considerations - Salomone, A; Bigiarini, R; Palamar, J J; McKnight, C; Vinsick, L; Amante, E; Di Corcia, D; Vincenti, M (Journal of analytical toxicology, 2020)
Abstract The detection of new psychoactive substances (NPS) in hair has become extensively researched in recent years. Although most NPS fall into the classes of synthetic cannabinoids and designer cathinones, novel synthetic opioids (NSO) have appeared with increasing frequency in the illicit drug supply. While the detection of NSO in hair is now well documented, interpretation of results presents several controversial issues, as is quite common in hair analysis. In this study, an ultra-high-performance liquid chromatography-tandem mass spectrometry method able to detect 13 synthetic opioids (including fentanyl analogs) and metabolites in hair was applied to 293 real samples. Samples were collected in the USA between November 2016 and August 2018 from subjects who had reported heroin use in the past year or had already tested positive to hair testing for common opiates. The range, mean and median concentrations were calculated for each analyte, in order to draw a preliminary direction for a possible cut-off to discriminate between exposure to either low or high quantities of the drug. Over two-thirds (68%) of samples tested positive for fentanyl at concentrations between LOQ and 8600 pg/mg. The mean value was 382 pg/mg and the median was 95 pg/mg. The metabolites norfentanyl and 4-ANPP were also quantified and were found between LOQ and 320 pg/mg and between LOQ and 1400 pg/mg, respectively. The concentration ratios norfentanyl/fentanyl, 4-ANPP/fentanyl and norfentanyl/4-ANPP were also tested as potential markers of active use and to discriminate the intake of fentanyl from other analogs. The common occurrence of samples positive for multiple drugs may suggest that use is equally prevalent among consumers, which is not the case, as correlations based on quantitative results demonstrated. We believe this set of experimental observations provides a useful starting point for a wide discussion aimed to better understand positive hair testing for fentanyl and its analogs in hair samples.